Resiliensi Bisnis Badan Usaha Milik Desa Pada Era Pandemi: Sebuah Pendekatan Studi Kasus - I Wayan Suartana; Gerianta Wirawan Yasa; Ni Putu Wiwin Setyari; I Gusti Ayu Purnamawati (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2020)
Business resilience is a manifestation of how an economic structure can survive and adapt to the empowerment of BUMDesa. This study aims to create a model for institutional capacity building for the success of BUMDesa in Bali. There are 455 BUMDesa in Bali that are engaged in various productive sectors, so the approach used in this study is a combination of qualitative and quantitative approaches. The qualitative approach is a case study. The quantitative approach is descriptive by displaying statistical data in the form of trends. The sampling technique was carried out by quota. There are eight districts and one city in Bali. Each will be given a quota by conducting random sampling in each district/city. The results showed that the stimulus funds and business planning can be a resilience modle for BUMDes. These two prerequisites must be fulfilled for BUMDesa in Bali so that they can continue to exist and show their identity in the midst of the current economic situation and downturn.